Serdexmethylphenidate/dexmethylphenidate for children with attention-deficit/hyperactivity disorder: dose optimization from a laboratory classroom study - Cutler, Andrew J.; Kollins, Scott H.; Brams, Matthew N.; Corliss, Meg; Oh, Charles; Braeckman, Rene; Childress, Ann C. (Frontiers in Psychiatry, 2024)
Objective: To evaluate treatment responder rate using the Attention-Deficit/Hyperactivity Disorder Rating Scale-5 (ADHD-RS-5) score based on optimized dose level of serdexmethylphenidate/dexmethylphenidate (SDX/d-MPH) and changes in ADHD severity in children (aged 6-12 years) with ADHD.Methods: During a 21-day dose-optimization phase, 155 patients initiated treatment with 39.2/7.8 mg SDX/d-MPH in the first week and then were titrated to an optimum dose; 5 patients were downtitrated to 26.1/5.2 mg, 76 were uptitrated to 52.3/10.4 mg, and 69 remained at 39.2/7.8 mg during the following 2 weeks. Responder threshold values were 30% and 50% based on the percent change from baseline (day 0) to days 7, 14, and 21 in the ADHD-RS-5 score. The Conners 3rd Edition-Parent score was used to assess weekly changes in ADHD severity during the doseoptimization and treatment phases.Results: Of the 5 subjects optimized at 26.1/5.2 mg, ≥80% across all days had ≥50% responder rate. Of the 69 subjects optimized at 39.2/7.8 mg, 81.2% had ≥50% responder rate by day 21. Of the 76 subjects optimized to 52.3/10.4 mg, 72.4% had ≥50% responder rate by day 21. Changes in ADHD severity, based on mean Conners 3rd Edition-Parent scores, improved from baseline at each visit during dose optimization for each subscale. At the dose-optimization phase, Conners 3rd Edition-Parent scores improved from baseline for SDX/d-MPH in all subscales. Conclusion: A high percentage of subjects were responders upon reaching their final optimized dose. SDX/d-MPH demonstrated significant reductions in ADHD severity in children based on the Conners 3rd Edition-Parent scores. Determining the optimal dosage of SDX/d-MPH and its effect on ADHD severity could enable the development of a more clinically relevant treatment regimen in children with ADHD.